Ultrasound‐Assisted Synthesis and Antioxidant Activity of 3‐Selanyl‐1 H‐indole and 3‐Selanylimidazo[1, 2‐a]pyridine Derivatives. Issue 11 (12th September 2017) - Vieira, Beatriz M.; Thurow, Samuel; da Costa, Monaliza; Casaril, Angela M.; Domingues, Micaela; Schumacher, Ricardo F.; Perin, Gelson; Alves, Diego; Savegnago, Lucielli; Lenardão, Eder J.
Abstract: A simple and rapid method for the selective synthesis of 3‐(organylselanyl)‐1 H ‐indoles and 3‐(organylselanyl)imidazo[1, 2‐ a ]pyridines catalyzed by CuI/SeO2 under ultrasound irradiation was developed. This protocol employs a diverse range of 1 H ‐indoles or imidazo[1, 2‐ a ]pyridines and diorganyl diselenides to afford the corresponding products selectively in good to excellent yields. Moreover, the antioxidant activity of these compounds was evaluated by using a wide range of in vitro assays, such as 2‐azinobis‐3‐ethylbenzothiazoline‐6‐sulfonic acid (ABTS), 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical, ferric ion reducing antioxidant power (FRAP), and inhibition of reactive species formation in mice cortex. The bioassays revealed that both classes of the newly synthesized organoselenium compounds present antioxidant activity, with emphasis on the 3‐(organylselanyl)‐1 H ‐indoles. This pharmacological activity opens a wide range of biological applications where the reduction of oxidative stress is essential. Abstract : Antioxidant organoselenium compounds : A simple and rapid method for the selective synthesis of 3‐(organylselanyl)‐1 H ‐indoles and 3‐(organylselanyl)imidazo[1, 2‐ a ]pyridines catalyzed by CuI/SeO2 under ultrasound irradiation was developed. This protocol employs a diverse range of 1 H ‐indoles or imidazo[1, 2‐ a ]pyridines and diorganyl diselenides to afford the corresponding products selectively in good to excellent yields, the antioxidant activity of which was evaluated by using a wide range of in vitro assays.